DATA model for a multidimensional decision making in healthcare. (2016) - Petrillo, Antonella; Felice, Fabio De; Petrillo, Laura
Health technology assessment (HTA) is increasingly used in European countries to inform decision and policy making in the healthcare sector. Several countries have integrated HTA into policy, governance or regulatory processes. The present research aims to propose a new multidisciplinary approach to support and to justify decisions policies in healthcare organisations for the standardisation of HTA information and for the achievement of a more quality decisions under uncertainty, which ultimately determines the success of organisations. A multidimensional model, called DATA model - decision analytic technology assessment model - based on analytic hierarchy process and the Cyert-March-Simon model (aka Carnegie decision model) is developed. The results obtained show the potentiality of the proposed approach in prioritising critical aspects and in supporting management performance quality in healthcare system.